HARMONIZING GLOBALIZATION: A STUDY ON HYBRIDIZATION THEORY AND POLYCENTRIC GOVERNANCE APPROACHES - Zhang, Xianyu; Minghua , Li (Top Journal of Public Policy and Administration (TJPPA), 2023)
This paper presents a hybridization theory of organization to explain the diversity of organizations in reality. It argues that all organizations are hybrid, as they combine elements of hierarchy, market, and network. The paper advocates for the division of labor and collaboration between hybrid organizations in delivering services, and polycentric governance in governing globalization. Drawing on transaction costs economics, the paper suggests that the governance structures of organizations vary to account for comparative advantages of economizing transaction costs in covenants and contracts. The case of transitional China is studied to explore the labor division and collaboration between corporate entities in the industries of education, healthcare and culture. The paper concludes that a polycentric order of governance that involves multiple levels and diverse types of organizations from the public, private, and third sectors with overlapping realms of responsibility and functional capacities is essential to cope with the challenges and opportunities of globalization.